Full-Length Genome Sequencing and Analysis of Hepatitis B Viruses Isolated from Iraqi Patients - Mamoori, Yaseen I.; Ahmed, Ibrahim A.; Mahmood, Ayhan R.; Al-Waysi, Safaa A. (International Journal of Microbiology, 2024)
Hepatitis B virus (HBV) causes liver diseases (chronic hepatitis, cirrhosis, and hepatocellular carcinoma) and is a leading health problem worldwide. Sequencing of the whole HBV genome provides insight into the virus genotype, subgenotype, serotype, genetic variation, and viral drug resistance. To date, no study has been conducted on the whole genome sequence of HBV obtained from Iraqi patients. Therefore, this is the first study to sequence clinical samples from these patients. Viral genomic DNA was isolated and amplified using five primer sets to amplify five overlapping regions covering the entire HBV genome. The amplicons were sequenced, aligned to a reference sequence, annotated, and submitted to the National Center for Biotechnology Information GenBank database. Sequence analysis showed that the genome size of the tested viral samples was 3,182 bp and belonged to genotype D, subgenotype D1, and serotype ayw2. Missense mutations were found in the four regions (X, PreS1-S, PreC-C, and P) of the tested samples, leading to amino acid substitutions, which were 8.4%, 5.1%, 4.7%, and 4.6%, respectively. These mutations may cause severe liver diseases.